Pharmacological characterization and antidiabetic activity of a long‐acting glucagon‐like peptide‐1 analogue conjugated to an antithrombin III‐binding pentasaccharide. Issue 8 (16th June 2015) - Patterson, S.; de Kort, M.; Irwin, N.; Moffett, R. C.; Dokter, W. H. A.; Bos, E. S.; Miltenburg, A. M. M.; Flatt, P. R.
<x xml:space="preserve">Abstract</x> Aims To examine the biological characteristics of a novel glucagon‐like peptide‐1 (GLP‐1) conjugate, in which an antithrombin III (ATIII)‐binding pentasaccharide is conjugated to d‐Ala8GLP‐1 using a tetraethylene glycol linker. Methods We assessed GLP‐1 receptor binding, cAMP generation and insulin secretory activity of the GLP‐1 conjugate in vitro. Circulating half‐life, glucose homeostatic and subchronic therapeutic effectiveness were then examined in vivo. Results The half‐life of the GLP‐1 conjugate in mice was ∼11 h. In vitro insulin secretion from clonal β cells and islets was increased (p < 0.001) by the conjugate. The conjugate had half maximum effective concentration values of 1.3 × 10−7 and 9.9 × 10−8 M for displacement of 125I‐GLP‐1 in competitive GLP‐1 receptor binding and cAMP generation, respectively. Glucose tolerance in normal mice, immediately and 4 h after conjugate injection, resulted in significant (p < 0.001) improvements in blood glucose. These effects persisted for >48 h after administration. Daily treatment (21 days) of high‐fat‐fed and ob/ob mice with 25 nmol/kg conjugate resulted in significant improvement in glucose tolerance (p < 0.001) and reductions in glycated haemoglobin (HbA1c; p < 0.01) equivalent to or better than with exenatide or liraglutide. Treatment of C57BL/KsJ db/db mice for 15 days with 100 nmol/kg conjugate significantly (p < 0.001) reduced glucose and raised plasma insulin. Oral glucose tolerance was significantly (p < 0.001) improved and both 24‐h glucose profile (p < 0.001) and HbA1c levels (p < 0.001) were reduced. Islet size (p < 0.001) and pancreatic insulin content were increased without change of islet cell proliferation or apoptosis. Conclusion These data show that d‐Ala8GLP‐1(Lys37) pentasaccharide exerts significant antidiabetic actions and has a projected pharmacokinetic/pharmacodynamic profile that merits further evaluation in humans for a possible once‐weekly dosing regimen.